Identification of Precast Parapet Work Activities in Elevated Railway Construction - Pungky Dharma Saputra (Applied Research on Civil Engineering and Environment (ARCEE), 2021)
Railway infrastructure development is very massive in Indonesia. Many projects have been constructing since 2013, such as the Mass Rapid Transit (MRT), Light Rail Transit (LRT), Double-Double Track (DDT), and High-Speed Rail (HSR). And all of these projects were design with elevated structures. When applying precast parapet panel technology in the MRT project elevated section, the contractor didn’t have a reference for precast parapet work activities. Hence, it required new planning for its construction and took time. The project sample of this research was MRT Jakarta CP 103 Project. There were three stages in this research starting from documentation analysis, expert judgment, and respondent survey. There were 5 bridge construction experts and 30 respondents which were professional engineers asked for their recommendations and opinions. Descriptive analysis was applied to know the percentage of opinions. This research focuses on identifying precast parapet activities in elevated railway construction project. There are 14 activities that had been identified in this research, namely preparation, position survey, adjustment material installation, precast parapet panel shifting from trailer to the top of deck slab, precast parapet panel distribution, precast parapet panel installation, rebar parapet installation for concrete stitch, sealing work, concrete casting, formwork dismantling, and finishing. These activities will be very useful for similar precast parapet works in a future project.